Senior High School Students' Comprehension and Interest in Science Content: Example of Participating in First-Hand Experimental Activities - Hsieh, Pei-Hsuan (Journal of Science and Technology, 2017)
The purpose of this study is to investigate three questions: First, it examines whether students' understanding of science increases after exposure to scientific content with animations and the provision of experience with practical scientific activities. Second, according to the Kolb Scale, an effort is made to determine which type of learning characteristics lead to higher degrees of understanding of science after engaging in practical scientific activities. Third, the study is used to investigate whether student willingness to engage in science-related work in the future is correlated with their levels of understanding of science. A total of 154 students from six senior high schools were invited to be participants. The results showed that most of the students exhibited significant improvement in their understanding of science after they were involved in actual experimental processes with animated content. The students having accommodator-type learning characteristics had higher levels of understanding of science as well as greater willingness to pursue science-related work in the future. However, the results indicated that legitimate experimental processes may help enhance student comprehension in terms of scientific content. There is no indication that they affect arousal of scientific interest and willingness to follow a science-related path as a future career.